Qualidade de vida em indivíduos com doença renal crônica em tratamento dialítico - Jesus, Nadaby Maria de (2018)
Introduction: Chronic Kidney Disease (CKD) is responsible for numerous negative repercussions on the physical and biopsychosocial aspects of the quality of life of its patients. And the dialysis treatment intensifies this impact. Objectives: To measure the quality of life of individuals with CKD; to compare whether there is a statistical difference between QoL in patients with CKD in relation to a normative group and to identify which social, demographic and clinical determinants are associated with the best QoL between these groups. Method: A cross-sectional, analytical and descriptive study, with a quantitative approach and approved by the local Ethics Committee. Performed in a public institution and a private hemodialysis clinic, in a municipality in the interior of Minas Gerais. There were two categories of participants, one study group (patients with CKD on hemodialysis) and one normative group (general population). The sociodemographic and clinical characterization questionnaires and WHOQOL-Bref were applied. We used statistical tests according to the variables of interest. We adopted a significance level of 0.05. Results: In the study group, there was a predominance of men (59%), incomplete high school education level (68%) and 55% said they did not have a married partner. The majority (53%) were from a private institution and 57% reported having some kind of complication. The variables age, marital status and schooling were different between groups (p <0.05). The results of the Whoqol-Bref study showed that only the physical and psychological domains were different between groups (p <0.05). The total QOL score of the hemodialysis group was 57.14 and the normative group was 71.43 (p <0.001). In the comparison between the two groups, the variables that most interfered with QOL were: smoking (domain "perception of quality of life") (Bi = -0.4061; p = 0.032); to perform hemodialysis (domain "satisfaction with health") (Bi = - 0.3029, p = 0.034); hemodialysis (Bi = -14.07 and p = <0.001) ("physical domain"); hemodialysis ("psychological domain") (Bi = -5.26 and p = 0.025); living together with another person (in the domain "social relations") (Bi = 5.22 and p = 0.041); (Bi = 5.4504, p = 0.011) and income (Bi = 0.0016, p = 0.018) (in the "Environment" domain). The variables that most interfered with the QOL in the hemodialysis group were: having a conjugal partner (Bi = 0.379, p = 0.042), income (Bi = 0, p = 0.006), doing hemodialysis in the public service (Bi = -0.513; p = 0.007) and smoking (Bi = -0.527; p = 0.039) (domain "perception of quality of life"); to perform hemodialysis in public service (domain "satisfaction with health") (Bi = -0.626; p = 0.003); (Bi = -3.951, p = 0.019), hemodialysis in public service (Bi = -7,024, p = 0,044), schooling (Bi = 10,391, p = 0,01), age (Bi = 0,23; p = 0.05), number of people in the residence (Bi = 2.292, p = 0.036) and hemodialysis session time (Bi = 0.222, p = 0.002) ("physical domain"); (Bi = 12.368, p = 0.001), income (Bi = -4.166, p = 0.002) and hemodialysis in public service (Bi = -11.0, p = 0.001) ("psychological domain"); age (Bi = 0.286, p = 0.02) and time of hemodialysis sessions (Bi = 0.291; p = <0.001) ("social relationships"); (Bi = 11,302, p = 0.001), age (Bi = 0.367, p = <0.001) and time of hemodialysis sessions (Bi = 0.117; p = 0.039) (environment domain). Conclusion: The total WHOqol score of the group of patients with CKD on hemodialysis were significantly lower compared to the normative group. Several social and demographic variables influence, both positively and negatively, on the QoL scores and should be considered in the clinical evaluation of these patients.